Identification of duplicate accessions in the sweet maize collection by means of zein electrophoresis - V. V. Sidorova; Yu. A. Kerv; A. V. Konarev (Вавиловский журнал генетики и селекции)
Of all the subspecies of Zea mays L. cultivated in the world, sweet maize is the most important for the global economy. The leading seed-growing companies and research institutions around the world are engaged in breeding this crop. To meet the increasing demands of the industry to grain quality, it is important to select appropriate local varieties and lines for hybridization. Local (usually heterogeneous) varieties are a valuable source material for creating self-pollinated lines that contribute to a significant broadening of the genetic base of parental forms used in breeding. The advantages of sweet maize varieties and the interest of the food industry in them make it possible to consider accessions from the maize collection of the N.I. Vavilov Institute (VIR) as a potentially valuable source material for breeding. The present research concentrated on 19 local sweet maize varieties with different grain colors from the VIR collection, that is, 9 varieties with the blue color of ripe grain, 4 with white (colorless) grain, 3 with yellow, and 3 with red. The research included an analysis of zein electrophoretic patterns (protein markers); a study of their biotype composition and the nature of genetic polymorphism, as well as the creation of a protein pattern database for each accession. For a series of accessions with the same varietal name, but different catalog numbers, the degree of their identity was determined from their biotype composition in order to exclude duplication. Zein electrophoresis was carried out in vertical plates of 10 % polyacrylamide gel according to the standard ISTA technique developed with the participation of the Biochemistry and Molecular Biology Department of VIR. Zein patterns were used for the first time to electrophoretically study sweet maize varieties with different grain colors. Unique zein patterns were established for all the accessions studied, which makes possible their identification by specific marker components. The results of this work characterize zein electrophoresis as a useful tool for the identification and registration of duplicate accessions in the VIR collection of sweet maize varieties.